IMPLEMENTATION OF HEALTH TRANSFORMATION IN PRIMARY SERVICES THROUGH IPC AND IPE INTEGRATED PKLT - Darwis Darwis; Eliana Eliana; Linda Linda; Emy Yuliantini; Sri Yanniarti; Yusmidiarti Yusmidiarti; Meriwati Mahyuddin; Erni Buston; Sahidan Sahidan (SEAN Institute, 2023)
The purpose of community service is to increase the knowledge and understanding of citizens to reduce the risk of non-communicable diseases, (Hypertension, Diabetes Militus, and Asthma) high risk of infectious diseases, (TB and Scabies) adolescent health risks. Family Planning (KB) program, risk of pregnant women and SEZ, risk of illness in toddlers. This activity will be a forum for learning and community service with the Inter Professional Collaboration (IPC) and Inter Professional Education (IPE) approaches. This activity is packaged in the form of an integrated PKLT in all fields of health at the Poltekkes Kemenkes Bengkulu, with counseling activities on infectious and non-communicable diseases, BB, TB, LiLa, TD, Blood Sugar, Hb and health status, packaged in the form of Posbindu, Posyandu and group counseling and mutual assistance, the results of the activity found hypertensive elderly 45% DM elderly 12.5%, obese mothers 67%, None of the adolescents were anemic, with a short category of 7.7% and thin 14.4% This devotion created a collaboration between the Kelurahan Penurunan, the Puskesmas Penurunan, the Lecturers and Students of the Poltekkes Kemenkes Bengkulu. It is hoped that all activities that have been carried out can continue to be carried out regularly in order to create a healthy community.